Time-Varying Risk Premium and Unemployment Risk across Age Groups - Mitra, Indrajit; Xu, Yu (Review of Financial Studies, 2020)
Abstract We show that time-varying risk premium in financial markets can explain a key, yet puzzling, feature of labor markets: the large differences in unemployment risk across worker age groups over the business cycle. Our search model features a time-varying risk premium and learning about unobserved heterogeneity in worker productivity. Their interaction generates large real effects through firms’ labor policies. Our model predicts higher unemployment risk of younger workers relative to prime-age workers when risk premium is high, and the employment ratio of prime-age to young workers to be more cyclical in high beta industries. We find empirical support for these predictions. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.